Congenital absence of the portal vein with splenomegaly in a young woman (Case Report) (Medical Journal of Indonesia, 2005)
Congenital Absence of the Portal Vein (CAPV) is a rare anomaly in which the intestinal and splenic venous drainage bypasses the liver and drains into the systemic veins through various venous shunts. We present a case of a 32-year-old woman with this malformation, the patient experienced hematemesis and melena repetitively and had splenomegaly and hypersplenism. The angiography demonstrated absence of portal vein. Splenectomy was performed to reduce the pressure of the veins around stomach and to correct the hypersplenism. In endoscopy examination six months after surgery, the esophageal varices had disappear and the size of gastric varices had decrease. (Med J Indones 2005; 14: 122-7) Keywords: Congenital absence of portal vein, splenomegaly, hypersplenism, hematemesis and melena